If my equation is 6m + 4 = 14

What does m equal?

11 answers

To solve the equation \( 6m + 4 = 14 \), follow these steps:

  1. Subtract 4 from both sides of the equation to isolate the term with \( m \):

    \[ 6m + 4 - 4 = 14 - 4 \]

    This simplifies to:

    \[ 6m = 10 \]

  2. Next, divide both sides by 6 to solve for \( m \):

    \[ m = \frac{10}{6} \]

  3. Simplifying the fraction:

    \[ m = \frac{5}{3} \]

So, \( m \) equals \( \frac{5}{3} \).

If my equation is 6m + 4 = 13
What does m equal?

To solve the equation \( 6m + 4 = 13 \), follow these steps:

  1. Subtract 4 from both sides of the equation:

    \[ 6m + 4 - 4 = 13 - 4 \]

    This simplifies to:

    \[ 6m = 9 \]

  2. Next, divide both sides by 6 to solve for \( m \):

    \[ m = \frac{9}{6} \]

  3. Simplifying the fraction:

    \[ m = \frac{3}{2} \]

So, \( m \) equals \( \frac{3}{2} \) or 1.5.

4 • 5/4

To multiply \( 4 \) by \( \frac{5}{4} \):

\[ 4 \cdot \frac{5}{4} = \frac{4 \cdot 5}{4} = \frac{20}{4} = 5 \]

So, \( 4 \cdot \frac{5}{4} = 5 \).

4 • (2 + 2n)

To simplify the expression \( 4 \cdot (2 + 2n) \), you can use the distributive property:

\[ 4 \cdot (2 + 2n) = 4 \cdot 2 + 4 \cdot 2n \]

Calculating each term:

\[ 4 \cdot 2 = 8 \] \[ 4 \cdot 2n = 8n \]

Putting it all together, the expression simplifies to:

\[ 8 + 8n \]

So, \( 4 \cdot (2 + 2n) = 8 + 8n \).

5 + (3 + 3n)

To simplify the expression \( 5 + (3 + 3n) \), you can combine like terms:

\[ 5 + (3 + 3n) = 5 + 3 + 3n \]

Now, combine the constant terms:

\[ 5 + 3 = 8 \]

So, the expression simplifies to:

\[ 8 + 3n \]

Thus, \( 5 + (3 + 3n) = 8 + 3n \).

2 • 4/2

To calculate \( 2 \cdot \frac{4}{2} \):

  1. Start with the fraction:

    \[ \frac{4}{2} = 2 \]

  2. Now multiply:

    \[ 2 \cdot 2 = 4 \]

So, \( 2 \cdot \frac{4}{2} = 4 \).